InSAR Offset Tracking Performance in Open-Pit Mine Deformation Validated by DEMs from TLS Data : A Case Study of Pit X, PT. Berau Coal - Widitomo, Danang; Hayati, Noorlaila (Syntax Corporation, 2025)
Coal is a fossil fuel with abundant reserves, including in Indonesia, making it a key energy resource. To maximize efficiency and profitability, the mining industry continues to rely on open-pit mining methods. However, this approach inherently creates mining slopes that are susceptible to instability. Slope failures not only disrupt operations but also lead to coal loss and increased operational costs. Therefore, monitoring slope deformation is essential for risk management and safety. This study explores the use of Interferometric Synthetic Aperture Radar (InSAR), specifically the offset tracking method applied to Sentinel-1A imagery, as an alternative for short-term monitoring of mine deformation. The method demonstrated its effectiveness by accurately detecting deformation at the landslide site, as confirmed by Digital Elevation Models (DEMs) taken before and after the event on February 22, 2022. The observed ground movement was directed toward the southwest and northwest, indicating a high landslide potential. Additionally, Terrestrial Laser Scanning (TLS) measurements estimated the volume of displaced material along the mine wall to be approximately 28,923.60 m3.